Towards Addressing the Opportunities and Challenges of Web 2.0 for Health and Informatics - Murray, P. J.; Cabrer, M.; Hansen, M.; Paton, C.; Elkin, P. L.; Erdley, W. S. (Yearbook of Medical Informatics, 2008)
ObjectiveTo provide an overview of Web 2.0 and Health 2.0, and so facilitate a widespread discussion of the nature of these concepts and their possible application within the health domain, and implications for health and biomedical informatics and for IMIA.MethodsIMIA, the International Medical Informatics Association, has established a Web 2.0 Exploratory Taskforce to bring together interested individuals from within and outside IMIA to explore the nature and potential of Web 2.0 applications. The Taskforce aims to develop background materials and sample uses of Web 2.0 applications, so as to propose specific lines of action for the IMIA Board and General Assembly. This paper provides a brief overview of Web 2.0 and related concepts, and examples of general and health-specific Web 2.0 applications. Some examples of the issues, challenges and opportunities are introduced, to set the scene for a wider dialogue on if, how, and how best, IMIA, and the wider health and informatics communities, should use these new applications and approaches.Results and conclusionsThis brief paper provides an introduction to, and overview of, the many issues involved in considering the application of Web 2.0 to health and informatics. All interested individuals and organisations are invited to use this as a starting point for engaging in wider discussion and contributing to the Taskforce and to IMIA’s future.
Keywords: IMIA; health informatics; medical informatics; Web 2.0; Health 2.0